2016
DOI: 10.1523/jneurosci.3485-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Neuromuscular Transmission May Underlie Motor Dysfunction in Spinal and Bulbar Muscular Atrophy

Abstract: Spinal and bulbar muscular atrophy (SBMA) in men is an androgen-dependent neuromuscular disease caused by expanded CAG repeats in the androgen receptor (AR). Whether muscle or motor neuron dysfunction or both underlies motor impairment in SBMA is unknown. Muscles of SBMA mice show significant contractile dysfunction, implicating them as a likely source of motor dysfunction, but whether disease also impairs neuromuscular transmission is an open question. Thus, we examined synaptic function in three well-studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 64 publications
8
52
0
Order By: Relevance
“…Recently, the skeletal muscle specific overexpression of IGF-1, or the silencing of mutant AR, was shown to rescue the phenotypes of SBMA model mice, suggesting the involvement of skeletal muscles in the neurodegeneration in SBMA [12,13,38]. Moreover, by analyzing NMJs in the SBMA model mice, pathological fragmentation of NMJs and abnormal synaptophysin distribution, as well as defects in the neuromuscular synaptic transmission, were demonstrated, which is consistent with the previously reported insufficient synaptic functions in SBMA [14,48]. Interestingly, our transcriptome analysis of iPSC-MNs revealed upregulation of synapse-related gene sets in the SBMA-MNs, including activation of intracellular signaling via calcium ions, formation of synaptic vesicles, and the release of neurotransmitters such as acetylcholine.…”
Section: Identification Of Cytokines and Neurotrophic Factors Involvesupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, the skeletal muscle specific overexpression of IGF-1, or the silencing of mutant AR, was shown to rescue the phenotypes of SBMA model mice, suggesting the involvement of skeletal muscles in the neurodegeneration in SBMA [12,13,38]. Moreover, by analyzing NMJs in the SBMA model mice, pathological fragmentation of NMJs and abnormal synaptophysin distribution, as well as defects in the neuromuscular synaptic transmission, were demonstrated, which is consistent with the previously reported insufficient synaptic functions in SBMA [14,48]. Interestingly, our transcriptome analysis of iPSC-MNs revealed upregulation of synapse-related gene sets in the SBMA-MNs, including activation of intracellular signaling via calcium ions, formation of synaptic vesicles, and the release of neurotransmitters such as acetylcholine.…”
Section: Identification Of Cytokines and Neurotrophic Factors Involvesupporting
confidence: 89%
“…Interestingly, recent analyses have shown that phenotypes and MN pathology of transgenic mice models were unexpectedly rescued by muscle-specific silencing of mutant AR, suggesting the involvement of muscle pathology in motor neuronal degeneration [12,13]. In addition, impaired transmission of neuromuscular synapses was observed in SBMA mice models [14]. These results strongly indicate muscular pathology, which causes neurodegeneration in SBMA.…”
Section: Introductionmentioning
confidence: 92%
“…Although motor neuron degeneration, occurs well after the first signs of muscle force deficits, it is important to acknowledge the possibility that motor neuron dysfunction may occur without degeneration (Katsuno et al, 2004) and in conjunction there may also be there also may be NMJ abnormalities (Xu et al, 2016). Late motor neuron degeneration or dysfunction may well be specific to the AR100 mice and the possibility exist that it may not reflect the scenario in SBMA patients.…”
Section: Disease Models and Mechanisms • Dmm • Accepted Manuscriptmentioning
confidence: 99%
“…There was no evidence of morphological denervation at the NMJ at 6 months of age in AR100 mice, the age where muscle force dysfunction first becomes evident. However, there may be functional denervation without morphological changes occurs at the NMJ (Poort et al, 2016;Xu et al, 2016). Although we have shown early dysfunction in motor neurons in AR100 mice, such as ER stress (Montague et al, 2014) and transcriptional dysregulation (Malik et al, 2019), we found that plasma levels of phosphorylated neurofilament heavy chain (pNfH), a marker of neuronal damage found to be altered in motor neuron disease such as ALS, was unchanged in SBMA patients and AR100 mice (Lombardi et al, 2019).…”
Section: Disease Models and Mechanisms • Dmm • Accepted Manuscriptmentioning
confidence: 99%
“…Loss of NAMPT in projection neurons alters skeletal muscle contractile responses. Disabled synaptic transmission in the motor terminal at the NMJ has been suggested to affect muscle function 35,36 . To NAD + levels in semitendinosus and gastrocnemius muscles of control mice after NMN administration.…”
Section: Loss Of Nampt In Projection Neurons Impairs Synaptic Endocytmentioning
confidence: 99%